If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 67.5 = -14.3u Solving 67.5 = -14.3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '14.3u' to each side of the equation. 67.5 + 14.3u = -14.3u + 14.3u Combine like terms: -14.3u + 14.3u = 0.0 67.5 + 14.3u = 0.0 Add '-67.5' to each side of the equation. 67.5 + -67.5 + 14.3u = 0.0 + -67.5 Combine like terms: 67.5 + -67.5 = 0.0 0.0 + 14.3u = 0.0 + -67.5 14.3u = 0.0 + -67.5 Combine like terms: 0.0 + -67.5 = -67.5 14.3u = -67.5 Divide each side by '14.3'. u = -4.72027972 Simplifying u = -4.72027972
| 6+9p-1=9p+68-7p | | 2x+6z=8 | | ab+c=5*c | | 21x-11=16x-6 | | 5w^2-23w+10=0 | | 12/17x=8 | | 12/15x=8 | | 5/6k-3/4=1/4 | | 5x+11=8x-19 | | 6+4=240 | | 18b=7b-20 | | 7(7X+1)=5(13X-21) | | X-2.4=11 | | 9x+y=-17 | | -0.5x^2+4x+10=0 | | 5h+5w= | | 5x+900-10x=640 | | 4x-3=14x+33 | | -6(x-1)-3x=7-9(x+2) | | 12(x-10)=3(x+4) | | B=21/0.3 | | -25-5x=2x+5 | | B=18/0.2 | | X-12=-20/x | | 7(9x-4)=4(3x+17) | | y=7tan(4x) | | 5x+39=14x+69 | | 3(x-4)=3x+4 | | 2-(3a-8)=1 | | 3(2x-3)-5=3(x-2)+4 | | -48-9x=7+16 | | j^2+16j-36=0 |